SME and information technology : a practical study of SMEs at the IT frontier (ITC GenevaCH, 2000)
Focuses on the role and importance of information technology in raising the competitiveness of small and medium-sized enterprises in the international market. Identifies critical factors preventing SMEs in developing countries from making optimal use of IT. Provides recommendations aimed at SME support institutions as a basis for designing technical assistance services for the business sector. Presents case studies illustrating active participation of trade support institutions in this area, in Africa, Asia and Latin America.
Keywords: SMALL ENTERPRISES